La devolución de evidencias en los delitos flagrantes y su incidencia en las víctimas - Saavedra Ordoñez, Jeimmy Lissette (2019)
The purpose of the present investigation was to evaluate the mechanism of immediate return of evidence found in the collection centers, evidence and evidence of the Judicial Police, in the canton of Guayaquil, Province of Guayas, Ecuador. With respect to the methodology used, the study focused on a positivist paradigm, with a quantitative and qualitative approach, descriptive, exploratory and explanatory. Therefore, for the data analysis we used the techniques of observation, measurement and interpretation of the results, which allowed to generate the synthesis and conclusions of this investigation. In this sense, the results are framed in that when analyzing the rights affected in the procedure of delivery of evidence, the violation of the rights of the victims is observed when the evidence that are the property of the victims is not returned until the criminal process is completed, which means that at this moment the victim must abandon their duties and responsibilities in order to resolve the return of their belongings……..